The Impact of the Positioning of Parts on the Variable Production Costs in the Case of Additive Manufacturing - Ficzere, Péter (Periodica Polytechnica Transportation Engineering, 2022)
Additive manufacturing is becoming increasingly widespread in many areas of life. One of the main reasons for this is that the machines, raw materials and manufacturing are becoming cheaper. The cheaper the technology, the more widespread it is. The cost of production is influenced by many factors. One of these shows the impact of the part's production positioning (placement in the working space) on costs in the following study. On this basis, we can simplify the traditional pricing strategy. From the results, we can determine how economically it is worth to place the parts in the work area of the machine.